INNOVATION IN THE DEVELOPMENT OF DIGITAL-BASED ISLAMIC RELIGIOUS EDUCATION CURRICULUM (CASE STUDY OF SMA MUHAMMADIYAH 1 YOGYAKARTA) - Widodo, Hendro; Haris, Yogi Sopian (POTENSIA: Jurnal Kependidikan Islam, 2026)
This research examines the innovation of digital-based ISMUBA curriculum development at SMA Muhammadiyah 1 Yogyakarta, driven by the need for educational transformation in the digital era. The main objective of the research is to analyze and describe a curriculum innovation model that can synergize pedagogical, technological, and spiritual aspects. This research uses a qualitative case study method, conducted through in-depth interviews, participatory observations, and document analysis to explore the integration of digital technology in the PAI curriculum. The research results show that the integration of digital literacy with Islamic values in the ISMUBA curriculum at SMA Muhammadiyah 1 Yogyakarta successfully creates students who are not only technically skilled but also wise in using technology. The use of online learning platforms, digital Quran applications, and interactive multimedia increases student engagement and motivation in religious studies. Teachers who are skilled in using technology also play an important role in delivering material in a more engaging and easily understandable manner. In addition, adequate infrastructure support and a school culture that fosters innovation are important factors in the success of this curriculum transformation. Although there are challenges related to technology access and teacher readiness, the solutions implemented, such as training and provision of facilities, can overcome these obstacleskeywords that are relevant to the research topic to help readers find articles through search engines.